Health Education About Hypertension Using Leaflet Media Effective On People's Knowledge And Attitudes Of The Community In Tanete Labba Hamlet, Maros - Jayadi, Yusma Indah; Maharani, Widia; Nurdiyanah, Nurdiyanah (Tadulako University, 2021)
Hypertension or high blood pressure is a serious medical condition that significantly increases the risk of heart, brain, kidney, and other diseases. In COVID-19 patients, Arterial Hypertension (AH) is one of the cardiovascular comorbidities that can worsen outcomes and increase the risk of admission to the intensive care unit (ICU). This study aims to measure the effectiveness of health education about hypertension and blood pressure checks using the media leaflet on the knowledge and attitudes of the community in Tanete Labba Hamlet, Maros.This research is a quasi-experimental research with Pre-test and Post-test without Control Group Design in Tanete Labba Hamlet, Baji Pa'mai Village, Cenrana District, Maros Regency. The population in this study were residents of Tanete Labba Hamlet, Baji Pa'mai Village, using purposive sampling method with inclusion criteria of population aged 15 years and never or rarely had their health checked so that a sample of 38 respondents was obtained. The analysis used is a paired T test. The purpose of this counseling is to provide information related to hypertension risk factors, symptoms of hypertension, control and prevention of hypertension, namely in the form of recommendations to control blood pressure regularly at least every 6 months. Health education with leaflet media had a significant effect on the level of knowledge p = 0.002 (p < 0.05) and the attitude of respondents p = 0.000 (p < 0.05) about hypertension and blood pressure checks. Most of the community gave a positive response to the material presented, enthusiastic in reading the contents of the leaflet and asking questions about hypertension and blood pressure checks. It is important that education and counseling programs are developed according to the needs of the community so that they can increase the knowledge of the general public and bring about positive changes in attitudes and practices.